Model Sosial Kognitif Perilaku Pencarian Informasi Akademik Secara Online - Risna Suminta, Rini; Luthfi Atmasari (Jurnal Studia Insania, 2025)
This study aims to test the cognitive social model of online academic information seeking behavior according to empirical data. The population in this study were all students of IAIN Kediri, East Java. The sampling technique in this study was simple random sampling. Simple random sampling means that researchers take subjects (or units such as schools) as members of the sample, which guarantees that regardless of the size of the sample, it will have an equal probability according to the population. The data collection technique used in this study was a questionnaire in the form of a scale. There are four types of scales used in the data collection process, namely social support scale, self-regulation scale, self-efficacy and online information seeking behavior scale. The results of this study showed that the chi-square was 144, 990 (DF= 83 p=0,000), CMIN/DF=1,747, GFI= 0,921, AGFI= 0,885, TLI= 0,913 and RMSEA = 0,061. Thus the criteria for acceptance of the model are generally met. Thus the relationship model can be said to be fit or the model can be fulfilled.